2014
DOI: 10.1111/liv.12691
|View full text |Cite
|
Sign up to set email alerts
|

P311 modulates hepatic stellate cells migration

Abstract: P311 is central to reactive oxygen species-mediated HSC migration induced by different chemokines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 40 publications
(43 reference statements)
1
13
0
Order By: Relevance
“…41 Several in vitro and in vivo studies have shown concrete evidences of HSCs migration toward the areas of tissue remodeling. 3,4 In this study, LX-2 cells exposed to SBN at increasing concentrations for 24 h in serum supplemented medium show a decrease in the migration of the LX-2 toward the scrap wound induced in the culture. This delaying process of HSCs migration toward wound area and the anti-proliferative responses of proliferating cells by SBN treatments could be utilized beneficially toward delaying hepatic fibrosis.…”
Section: Journal Of Clinical and Experimental Hepatologymentioning
confidence: 51%
See 1 more Smart Citation
“…41 Several in vitro and in vivo studies have shown concrete evidences of HSCs migration toward the areas of tissue remodeling. 3,4 In this study, LX-2 cells exposed to SBN at increasing concentrations for 24 h in serum supplemented medium show a decrease in the migration of the LX-2 toward the scrap wound induced in the culture. This delaying process of HSCs migration toward wound area and the anti-proliferative responses of proliferating cells by SBN treatments could be utilized beneficially toward delaying hepatic fibrosis.…”
Section: Journal Of Clinical and Experimental Hepatologymentioning
confidence: 51%
“…In vitro and in vivo studies have shown that proliferation and migration of HSCs toward the areas of tissue remodeling may be an additional factor contributing to wound healing and fibrosis. 3,4 Hence, prevention of HSC proliferation together with its migration toward the microenvironment of injury in the liver regarded as one of the key strategies to reduce the progression of hepatic fibrosis.…”
mentioning
confidence: 99%
“…Fibroblast migration is a key event for organ development as well as fibrosis ( Shimizu et al, 2001 ; Hattori et al, 2004 ; Scholten et al, 2011 ). P311 is described by different groups to play an important role during chemokine-induced cell migration ( Studler et al, 1993 ; Mariani et al, 2001 ; McDonough et al, 2005 ; Guimaraes et al, 2015 ). The first study ever describing P311 already detected the mRNA in migrating cells in the developing brain ( Studler et al, 1993 ).…”
Section: P311 Is Expressed In Migrating Cells and Stimulates The Rac1mentioning
confidence: 99%
“…This correlation between P311 and cell migration was also shown during liver fibrosis. Upon liver injury, hepatic stellate cells activate, resulting in contractile and migrating hepatic stellate cells with increased P311 transcription ( Guimaraes et al, 2015 ). When activated chronically, these cells deposit high levels of collagen, resulting in liver fibrosis and finally cirrhosis.…”
Section: P311 Is Expressed In Migrating Cells and Stimulates The Rac1mentioning
confidence: 99%
See 1 more Smart Citation